Thiourea-alginic acid polyolefin material ash removal agent as well as preparation method and application thereof

Through the use of ash removal agent for thiourea-alginic acid polyolefin material, the problem of difficult metal residue removal in polyolefin materials is solved, and the efficient and low-cost metal removal effect is achieved, and the service life of the adsorbent is extended.

CN119638866APending Publication Date: 2025-03-18HANGZHOU RUIFENGRONGCHUANG TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411910670.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove metal residues in polyolefin materials, resulting in the impact of the performance of the terminal product. The commonly used chelation adsorption methods have problems such as low payload, short service life and cumbersome operation.

Method used

Thiourea-alginic acid polyolefin material ash removal agent is used. The removal agent connects thiourea and alginic acid through chemical bonds to form a composite material with multiple active sites, which can effectively complex and remove metal ash.

Benefits of technology

It achieves extremely low control of the total metal ions content in polyolefin materials, avoids swelling and high pressure drop, extends the service life of adsorbent fillers, and improves the removal efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638866A_ABST
    Figure CN119638866A_ABST
Patent Text Reader

Abstract

The invention provides a thiourea-alginic acid polyolefin material ash removal agent. The thiourea-alginic acid polyolefin material ash removal agent has a structure shown in the following formula, wherein n is greater than or equal to 1; the preparation method comprises the following steps: mixing a condensation activator and an alginic acid aqueous dispersion, carrying out a reaction, adding thiourea and a condensing agent, continuing the reaction, and sequentially filtering, washing, precipitating and drying the obtained reactant to obtain the product. Or mixing alginic acid with N, N-dimethylformamide and thionyl chloride, carrying out a first reflux reaction, centrifuging to obtain acylating chlorination alginic acid, washing, mixing with thiourea and anhydrous tetrahydrofuran, and carrying out a second reflux reaction to obtain the product. When the thiourea-alginic acid polyolefin material ash removal agent is used for removing residual metal in polyolefin, the swelling phenomenon cannot be generated, pressure drop is low, operation is facilitated, the metal removal effect is good, the total content of metal ions in polyolefin can be controlled within an extremely low range, and compared with an existing chelating adsorption method, the thiourea-alginic acid polyolefin material ash removal agent has the advantage that the adsorption efficiency is high. The method has remarkable technical advantages. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyolefin material preparation, and more specifically to a thiourea-alginate polyolefin material ash removal agent. Background Art

[0002] Metal catalysts are required in the process of synthesizing polyolefin products by solution polymerization. The metal in the catalyst remains in the polyolefin product, which will have a negative impact on the appearance, dielectric properties, optical properties, weather resistance, etc. of the end product, seriously affecting the yield of the end product, and will also produce metal deposition and cause metal pollution. Therefore, for polyolefin products, especially high-end polyolefin products, how to efficiently remove metal residues (referred to as deashing) is a top priority.

[0003] The deashing methods commonly used in the polymer industrialization process mainly include aqueous phase extraction, coagulation sedimentation and chelate adsorption. Among them, chelate adsorption is the most commonly used deashing method in polymer industrial production, with the advantages of simple process, large adsorption capacity, high removal efficiency, few interference factors and good stability. Chelating agents are roughly divided into two categories: inorganic and organic. Inorganic chelating agents are usually easy to decompose at high temperatures and are only applicable to alkaline media, with a limited scope of application. Although organic chelating agents have a wide range of applications, it is usually difficult to remove the metal content in the polymer solution to below 10ppm. In addition, industrial processes often use loaded adsorbent fillers for chelating deashing, such as the polyolefin adsorbents disclosed in patents CN1044415A and CN104587962A. This type of adsorbent is a solid filler made by impregnating and calcining an alginate carrier and a chelating agent material. The effective loading amount of the chelating agent is low. When used for chelating adsorption to remove metal ions in a polyolefin solution, the chelating ability is limited and the service life is short. The adsorbent filler in the adsorption column needs to be replaced frequently, which is not only cumbersome to operate, but also causes a waste of the cost of alginate.

[0004] Therefore, it is urgent to develop a new type of ash removal agent and a corresponding polyolefin solution chelating deashing method to extend the service life of the adsorbent filler, shorten the replacement cycle of the adsorption column, and ensure a good chelating deashing effect. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a thiourea-alginate polyolefin material ash removal agent and a preparation method and application thereof. When the thiourea-alginate polyolefin material ash removal agent provided by the present invention is used to remove residual metals in polyolefins, not only does not produce swelling, but also has a low pressure drop that is conducive to operation, and has a good metal removal effect. The total content of metal ions in polyolefins can be controlled within an extremely low range. Compared with the existing chelating adsorption method, it has significant technical advantages.

[0006] The present invention provides a thiourea-alginate polyolefin material ash removal agent having a structure shown in Formula I:

[0007]

[0008] In formula I, n≥1.

[0009] The present invention also provides a method for preparing the thiourea-alginate polyolefin material ash removal agent described in the above technical solution, comprising the following steps:

[0010] The condensation activator and the alginic acid aqueous dispersion are mixed to react, and then thiourea and the condensation agent are added to continue the reaction, and the obtained reactants are filtered, washed, precipitated and dried in sequence to obtain a thiourea-alginic acid polyolefin material ash removal agent;

[0011] or,

[0012] Alginate is mixed with N,N-dimethylformamide and thionyl chloride for a first reflux reaction, and then centrifuged to obtain acyl chloride alginate, which is then washed and mixed with thiourea and anhydrous tetrahydrofuran for a second reflux reaction to obtain a thiourea-alginate polyolefin material ash removal agent.

[0013] Preferably, the condensation activator is selected from one or more of 4-N,N-dimethylaminopyridine, 1-hydroxybenzotriazole and 4-pyrrolidinylpyridine;

[0014] The mass ratio of the condensation activator to alginic acid is (0.0005-0.3):1.

[0015] Preferably, the condensing agent is selected from one or more of cyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide;

[0016] The mass ratio of the condensing agent to alginic acid is (0.001-0.1):1.

[0017] Preferably, the mass ratio of thiourea to alginate is (0.005-5):1.

[0018] Preferably, the reaction temperature is 40°C to 80°C, and the reaction time is 50min to 100min;

[0019] The temperature of the continued reaction is 50° C. to 100° C., and the time is 30 min to 150 min.

[0020] Preferably, the volume ratio of the thionyl chloride to the mass ratio of the alginate is (1 mL to 20 mL): 1 g;

[0021] The mass ratio of thiourea to acyl chloride alginic acid is (0.01-2):1.

[0022] Preferably, the temperature of the first reflux reaction is 40°C to 80°C, and the time is 12h to 24h;

[0023] The temperature of the second reflux reaction is 70° C. to 75° C., and the time is 18 h to 20 h.

[0024] The present invention also provides an application of an ash removal agent for removing metal ash in a polyolefin reaction liquid, wherein the ash removal agent is the thiourea-alginate polyolefin material ash removal agent described in the above technical scheme or the thiourea-alginate polyolefin material ash removal agent prepared by the preparation method described in the above technical scheme.

[0025] Preferably, the method comprises the following steps:

[0026] The ash removal agent is installed on the solid bed reactor, and the polyolefin reaction liquid is introduced at a reaction temperature of 50°C to 300°C. The flow rate of the polyolefin reaction liquid is 1mL / min to 10mL / min, and the mass ratio of the polyolefin reaction liquid treatment amount to the ash removal agent is (1000 to 100000):1.

[0027] The present invention provides a thiourea-alginate polyolefin material ash removal agent having a structure shown in Formula I:

[0028]

[0029] In formula I, n≥1. Compared with the prior art, the thiourea-alginate polyolefin material ash removal agent provided by the present invention does not produce swelling phenomenon when used to remove residual metals in polyolefins, has a low pressure drop and is convenient for operation, and has a good metal removal effect, and can control the total content of metal ions in polyolefins within an extremely low range. Compared with the existing chelating adsorption method, it has significant technical advantages. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a thiourea-alginate polyolefin material ash removal agent having a structure shown in Formula I:

[0032]

[0033] In formula I, n≥1.

[0034] In the present invention, thiourea and alginic acid are connected by chemical bonds to form a deashing agent for a polyolefin solution. Compared with the prior art, the deashing agent provided by the present invention has more active sites, can fully complex with metal ash, and effectively remove metal ash in polypropylene materials; at the same time, the deashing agent also has the advantages of simple preparation method, fast deashing rate, high removal rate of metal ions, large adsorption capacity, etc., and does not limit the basic ash content of polyolefin materials, and has a wide range of raw material sources; in addition, the deashing agent also has good stability, can meet the requirements of a fixed bed reaction device, and is not limited by the basic production process, and does not affect the stability and continuity of normal production.

[0035] The present invention also provides a method for preparing the thiourea-alginate polyolefin material ash removal agent described in the above technical solution, comprising the following steps:

[0036] The condensation activator and the alginic acid aqueous dispersion are mixed to react, and then thiourea and the condensation agent are added to continue the reaction, and the obtained reactants are filtered, washed, precipitated and dried in sequence to obtain a thiourea-alginic acid polyolefin material ash removal agent;

[0037] or,

[0038] Alginate is mixed with N,N-dimethylformamide and thionyl chloride for a first reflux reaction, and then centrifuged to obtain acyl chloride alginate, which is then washed and mixed with thiourea and anhydrous tetrahydrofuran for a second reflux reaction to obtain a thiourea-alginate polyolefin material ash removal agent.

[0039] In a preferred embodiment of the present invention, the preparation method of the thiourea-alginate polyolefin material ash removal agent comprises the following steps:

[0040] The condensation activator and the alginic acid aqueous dispersion are mixed and reacted, and then thiourea and the condensation agent are added to continue the reaction. The obtained reactants are filtered, washed, precipitated and dried in sequence to obtain the above-mentioned thiourea-alginic acid polyolefin material ash removal agent having the structure shown in formula I.

[0041] The reaction formula is as follows:

[0042]

[0043] In the present invention, the condensation activator is preferably selected from one or more of 4-N,N-dimethylaminopyridine, 1-hydroxybenzotriazole and 4-pyrrolidinylpyridine, and more preferably 4-N,N-dimethylaminopyridine, 1-hydroxybenzotriazole or 4-pyrrolidinylpyridine. The present invention has no particular restrictions on the sources of the condensation activator, alginic acid and thiourea, and commercially available products known to those skilled in the art can be used.

[0044] In the present invention, the mass ratio of the condensation activator to alginic acid is preferably (0.0005-0.3):1.

[0045] In the present invention, the reaction temperature is preferably 40° C. to 80° C., and the reaction time is preferably 50 min to 100 min.

[0046] In the present invention, the condensing agent is preferably selected from one or more of cyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, more preferably cyclohexylcarbodiimide, diisopropylcarbodiimide or 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide. The present invention has no particular restrictions on the source of the condensing agent, and commercially available products well known to those skilled in the art can be used.

[0047] In the present invention, the mass ratio of the condensing agent to alginic acid is preferably (0.001-0.1):1; the mass ratio of thiourea to alginic acid is preferably (0.005-5):1.

[0048] In the present invention, the temperature of the continued reaction is preferably 50° C. to 100° C., and the time is preferably 30 min to 150 min.

[0049] The present invention has no special restrictions on the filtering, washing, precipitation and drying processes, and can adopt technical means well known to those skilled in the art, with the purpose of obtaining a thiourea-alginate polyolefin material ash removal agent product.

[0050] In another preferred embodiment of the present invention, the preparation method of the thiourea-alginate polyolefin material ash removal agent comprises the following steps:

[0051] Alginate is mixed with N,N-dimethylformamide and thionyl chloride for a first reflux reaction, and then centrifuged to obtain chlorinated alginate, which is then washed and mixed with thiourea and anhydrous tetrahydrofuran for a second reflux reaction to obtain the above-mentioned thiourea-alginate polyolefin material ash removal agent having a structure shown in Formula I.

[0052] The reaction formula is as follows:

[0053]

[0054] The present invention has no special restrictions on the sources of the alginic acid, N,N-dimethylformamide, thionyl chloride, thiourea and anhydrous tetrahydrofuran, and commercially available products known to those skilled in the art can be used.

[0055] In the present invention, the mass ratio of the volume of thionyl chloride to alginate is preferably (1 mL to 20 mL): 1 g.

[0056] In the present invention, the temperature of the first reflux reaction is preferably 40° C. to 80° C., and the time is preferably 12 h to 24 h.

[0057] In the present invention, the mass ratio of thiourea to acyl chloride alginic acid is preferably (0.01-2):1.

[0058] In the present invention, the temperature of the second reflux reaction is preferably 70° C. to 75° C., and the time is preferably 18 h to 20 h.

[0059] The preparation method provided by the invention has a clear and simple process route, mild and easily controllable conditions, and has broad application prospects.

[0060] The present invention also provides an application of an ash removal agent for removing metal ash in a polyolefin reaction liquid, wherein the ash removal agent is the thiourea-alginate polyolefin material ash removal agent described in the above technical scheme or the thiourea-alginate polyolefin material ash removal agent prepared by the preparation method described in the above technical scheme.

[0061] In the present invention, the method for removing metal ash in a polyolefin reaction solution preferably comprises the following steps:

[0062] The ash removal agent is installed on the solid bed reactor, and the polyolefin reaction liquid is introduced at a reaction temperature of 50°C to 300°C. The flow rate of the polyolefin reaction liquid is 1mL / min to 10mL / min, and the mass ratio of the polyolefin reaction liquid treatment amount to the ash removal agent is (1000 to 100000):1.

[0063] In the present invention, the ash removal agent is the thiourea-alginate polyolefin material ash removal agent described in the above technical solution or the thiourea-alginate polyolefin material ash removal agent prepared by the preparation method described in the above technical solution; the polyolefin reaction liquid is preferably a polypropylene reaction liquid.

[0064] Finally, ethanol was added to the reaction solution flowing out of the fixed bed reactor to precipitate the polymer, which was filtered and dried, and the metal ash content was tested.

[0065] The present invention provides a thiourea-alginate polyolefin material ash removal agent having a structure shown in Formula I:

[0066]

[0067] In formula I, n≥1. Compared with the prior art, the thiourea-alginate polyolefin material ash removal agent provided by the present invention does not produce swelling phenomenon when used to remove residual metals in polyolefins, has a low pressure drop and is convenient for operation, and has a good metal removal effect, and can control the total content of metal ions in polyolefins within an extremely low range. Compared with the existing chelating adsorption method, it has significant technical advantages.

[0068] In order to further illustrate the present invention, the following examples are provided for detailed description. In the following examples of the present invention, if no specific conditions are specified, the reaction is carried out according to conventional conditions or conditions recommended by the manufacturer, and if no manufacturer is specified for the reagents or instruments used, all of them are conventional products that can be purchased commercially.

[0069] The main raw material sources of the present invention are as follows:

[0070] Alginic acid, zinc oxide, magnesium oxide, calcium oxide, thiourea, 3,4-thiophenedicarboxylic acid, 3-methyl-2-thiophenecarboxylic acid, 3-thiophenecarboxylic acid, toluene, n-hexane, cyclohexane, ethanol, octene, and triisobutylaluminum were purchased from Alfa Aesar Chemicals;

[0071] rac-dimethylsilylbisindenyl zirconium dichloride was purchased from Beijing Inokai Technology Co., Ltd.;

[0072] Methylaluminoxane (MAO) was purchased from Chemtura Organometallics;

[0073] 2-Norbornene (NBE) and ethylidene norbornene (ENB) were purchased from Tokyo Chemical Industry Co., Ltd. (TCI);

[0074] Styrene was purchased from Sinopec Qilu Petrochemical Co., Ltd.;

[0075] Ethylene, propylene and butadiene were purchased from Air Liquide (Shanghai) Compressed Gas Co., Ltd.

[0076] The main testing methods involved in the present invention are as follows:

[0077] Specific surface area and pore size of the adsorbent: Micromeritics ASAP 2420 was used for testing at 77K using nitrogen adsorption and desorption.

[0078] Adsorbent density: The test was conducted using a Japanese Shimadzu high-precision electronic density analysis balance AUY120.

[0079] Total ion content in the sample: tested by Agilent inductively coupled plasma emission spectrometer (ICP), Agilent 8900, dual quadrupole detector, four-channel reaction cell for element qualitative and quantitative analysis.

[0080] The main parameters of the adsorption column involved in the present invention are as follows:

[0081] Adsorption column: Cylindrical adsorption column, made of 316L stainless steel, with dimensions of 40mm×400mm and a volume of 500mL.

[0082] The residence time calculation method involved in the present invention is as follows:

[0083] Residence time = (adsorption column volume - adsorbent effective filling volume) / polymer solution flow rate; wherein, adsorbent effective filling volume = adsorbent mass / adsorbent density.

[0084] Unless otherwise specified, the pressure conditions in the following embodiments are gauge pressure.

[0085] The present invention relates to a method for preparing a reaction solution as follows:

[0086] (1) Preparation of COC reaction liquid: 500 g of 2-norbornene and 2 L of purified toluene were added to a 5 L reactor, the reactor was heated to 70°C, and high-purity ethylene was introduced into the reactor until the pressure reached 0.5 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After 5 min of reaction, 1 mL of ethanol was added into the reactor through the feed bin and stirring was continued for 5 min to obtain COC reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of COC reaction liquid was added to 10 mL of ethanol to precipitate COC solid, and the solid was placed in a vacuum oven at 70°C and dried for 24 h. The total ion content in the solid was 13034 ppm according to ICP test.

[0087] (2) Preparation of COP reaction liquid: 100 g of 2-norbornene, 200 g of dicyclopentadiene, 200 g of tetracyclododecene, 0.32 g of 1-octene and 2 L of purified toluene were added to a 5 L reactor, and the reactor was heated to 70°C. After the pressure was balanced, 0.74 g of tungsten hexachloride, 4.5 g of triethylaluminum and 89 g of ethanol were added to the reactor through the feeding bin to initiate the polymerization reaction. After the reaction lasted for 120 min, 1 mL of ethanol was added to the reactor through the feeding bin and continued to stir for 5 min to obtain a COP reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of COP reaction liquid was taken and 10 mL of ethanol was added to precipitate COP solid, which was placed in a vacuum oven at 70°C and dried for 24 h. The total ion content in the solid was 12546 ppm according to ICP test.

[0088] (3) Preparation of POE reaction liquid: 300 g of octene and 2 L of purified toluene were added to a 5 L reactor, the reactor was heated to 100 ° C, and then high-purity ethylene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate the polymerization reaction. After the reaction time was 5 min, 1 mL of ethanol was added into the reactor through the feed bin and the stirring was continued for 5 min to obtain a POE reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of POE reaction liquid was added to 10 mL of ethanol to precipitate POE solid, and the solid was placed in a vacuum oven at 70 ° C and dried for 24 h. The total ion content in the solid was 9142 ppm according to the ICP test.

[0089] (4) Preparation of LLDPE reaction liquid: 50 g of octene and 2 L of refined hexane were added to a 5 L reactor, the reactor was heated to 100 °C, and then high-purity ethylene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 g of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After 5 min of reaction, 1 mL of ethanol was added into the reactor through the feed bin and stirring was continued for 5 min to obtain LLDPE reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of LLDPE reaction liquid was taken and 10 mL of ethanol was added to precipitate LLDPE solid, which was placed in a vacuum oven at 70 °C and dried for 24 h. ICP test showed that the total ion content in the solid was 9571 ppm.

[0090] (5) Preparation of EPDM solution: 10 g of ENB and 2 L of refined hexane were added to a 5 L reactor, and the reactor was heated to 80 °C. Then, high-purity ethylene and propylene were introduced into the reactor at a flow rate ratio of 2:1 until the pressure reached 0.8 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 g of rac-dimethylsilylbisindenyl zirconium dichloride were added to the reactor through the feed bin to initiate the polymerization reaction. After the reaction lasted for 5 min, 1 mL of ethanol was added to the reactor through the feed bin and stirred for 5 min to obtain EPDM reaction solution. The discharge valve at the bottom of the reactor was opened, 10 mL of EPDM reaction solution was taken and 10 mL of ethanol was added to precipitate EPDM solid, which was placed in a vacuum oven at 70 °C and dried for 24 h. The total ion content in the solid was 10230 ppm according to ICP test.

[0091] (6) Preparation of SBR solution: 80 g of styrene and 2 L of refined cyclohexane were added to a 5 L reactor, the reactor was heated to 70 °C, and then high-purity butadiene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After the reaction for 5 min, 1 mL of ethanol was added into the reactor through the feed bin and stirred for 5 min to obtain an SBR reaction solution. The discharge valve at the bottom of the reactor was opened, 10 mL of the SBR reaction solution was added with 10 mL of ethanol to precipitate the SBR solid, which was placed in a vacuum oven at 70 °C and dried for 24 h. The total ion content in the solid was 10522 ppm according to ICP test.

[0092] Example 1

[0093] Preparation of adsorbent A-1:

[0094] 0.25 g of 1-hydroxybenzotriazole (HOBt) was added to 1 L of 50 mg / mL alginate aqueous dispersion at a reaction temperature of 60°C for 70 min. Then 30 g of 5-amino-8-hydroxyquinoline and 0.25 g of diisopropylcarbodiimide (DIC) were added to the dispersion to continue the reaction, and the reaction was stirred at 60°C for 80 min. After the reaction was completed, the mixed solution was filtered, the precipitate was fully washed, and dried to obtain deashing agent A-1.

[0095] Example 2

[0096] Preparation of adsorbent A-2:

[0097] 0.32g of 4-N,N-dimethylaminopyridine (DMAP) was added to 1L of 70mg / mL alginate aqueous dispersion for reaction at 60°C for 70min. Then 30g of 5-amino-8-hydroxyquinoline and 0.25g of diisopropylcarbodiimide (DIC) were added to the dispersion for further reaction at 70°C for 100min. After the reaction was completed, the mixed solution was filtered, the precipitate was fully washed, and dried to obtain deashing agent A-2.

[0098] Example 3

[0099] Preparation of adsorbent A-3:

[0100] 0.45 g of 4-pyrrolidinylpyridine (4-PPY) was added to 1 L of 80 mg / mL alginic acid aqueous dispersion for reaction at 75°C for 60 min. Then 35 g of 5-amino-8-hydroxyquinoline and 0.65 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI) were added to the dispersion for further reaction, and the reaction was stirred at 80°C for 90 min. After the reaction was completed, the mixed solution was filtered, the precipitate was fully washed, and dried to obtain deashing agent A-3.

[0101] Example 4

[0102] Preparation of adsorbent A-4:

[0103] 0.27g of 4-pyrrolidinylpyridine (4-PPY) and 0.28g of 4-N,N-dimethylaminopyridine (DMAP) were added to 1L of 80mg / mL alginate aqueous dispersion for reaction at 80°C for 50min. Then 35g of 5-amino-8-hydroxyquinoline and 0.65g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDCI) were added to the dispersion for further reaction, and the reaction was stirred at 80°C for 90min. After the reaction was completed, the mixed solution was filtered, the precipitate was fully washed, and dried to obtain deashing agent A-4.

[0104] Example 5

[0105] Preparation of adsorbent B-1:

[0106] First, 10g of alginic acid and 100mL of N,N-dimethylformamide were added to 100mL of thionyl chloride, and the mixture was reacted at 50°C for 18h. Then the reaction solution was centrifuged to obtain solid chlorinated alginic acid, which was washed several times with tetrahydrofuran. Then 10g of 5-amino-8-hydroxyquinoline and anhydrous tetrahydrofuran were added to the previously prepared chlorinated alginic acid, and refluxed at 70°C for 20 hours. After the reaction was completed, it was fully washed to obtain deashing agent B-1.

[0107] Example 6

[0108] Preparation of adsorbent B-2:

[0109] First, 15g of alginic acid and 80mL of N,N-dimethylformamide were added to 180mL of thionyl chloride, and the mixture was reacted at 60°C for 16h. Then the reaction solution was centrifuged to obtain solid chlorinated alginic acid, which was washed several times with tetrahydrofuran. Then, 15g of 5-amino-8-hydroxyquinoline and anhydrous tetrahydrofuran were added to the previously prepared chlorinated alginic acid, and refluxed at 75°C for 18 hours. After the reaction was completed, it was fully washed to obtain deashing agent B-2.

[0110] Example 7

[0111] Preparation of adsorbent B-3:

[0112] First, 15g of alginic acid and 80mL of N,N-dimethylformamide were added to 225mL of thionyl chloride, and the mixture was reacted at 60°C for 16h. Then the reaction solution was centrifuged to obtain solid chlorinated alginic acid, which was washed several times with tetrahydrofuran. Then, 15g of 5-amino-8-hydroxyquinoline and anhydrous tetrahydrofuran were added to the previously prepared chlorinated alginic acid, and refluxed at 75°C for 18 hours. After the reaction was completed, it was fully washed to obtain deashing agent B-3.

[0113] Comparative Example 1

[0114] Alginic acid was directly used as deliming agent C-1.

[0115] Comparative Example 2

[0116] 5-Amino-8-hydroxyquinoline was directly used as the deliming agent C-2.

[0117] The adsorbents provided in each embodiment and comparative example were filled into the adsorption column, and the effective filling volume of the adsorbent was 45 mL. The adsorption column was heated according to the operating conditions in Table 1, and the previously prepared COC reaction solution was passed through, and the flow rate of each polymer solution was adjusted to 6 mL / min by a liquid flow meter. Then, the same volume of ethanol was added to each polymer solution flowing out of the adsorption column, and the polymer was precipitated. After filtering, it was placed in a vacuum oven at 70 ° C and dried for 24 hours. The total ion content was tested by ICP and recorded in Table 1.

[0118] Table 1 Deashing effect of different adsorbents on COC solution

[0119]

[0120] The adsorbents provided in Example 7 were filled into the adsorption columns, and the effective filling volume of the adsorbent was 45 mL. The adsorption column was heated according to the operating conditions in Table 2, and the previously prepared polyolefin reaction solution was passed through, and the flow rate of each polymer solution was adjusted to 6 mL / min by a liquid flow meter. Then, the same volume of ethanol was added to each polymer solution flowing out of the adsorption column, and the polymer was precipitated. After filtering, it was placed in a vacuum oven at 70°C and dried for 24 hours. The total ion content was tested by ICP and recorded in Table 2.

[0121] Table 2 Deashing effect of deashing agent B-3 on different polyolefin solutions

[0122]

[0123] The adsorbents provided in Example 7 were filled into the adsorption columns respectively, and the effective filling volume of the adsorbent was 45 mL. The adsorption column was heated according to the operating conditions in Table 3, and the COC reaction solution prepared previously was passed through, and the flow rate of each polymer solution was adjusted to 6 mL / min by a liquid flow meter. Then, the same volume of ethanol was added to each polymer solution flowing out of the adsorption column, and the polymer was precipitated. After filtering, it was placed in a vacuum oven at 70 ° C and dried for 24 hours. The total ion content was tested by ICP and recorded in Table 3.

[0124] Table 3 Deashing effect of deashing agent B-3 on COC reaction solution at different temperatures

[0125]

[0126]

[0127] The adsorbents provided in Example 7 were filled into the adsorption columns, respectively, and the effective filling volume of the adsorbent was 45 mL. The adsorption column was heated according to the operating conditions in Table 4, and the COC reaction solution prepared previously was passed through, and the flow rate of the polymer solution described in Table 4 was adjusted by a liquid flow meter. Then, the same volume of ethanol was added to each polymer solution flowing out of the adsorption column, and the polymer was precipitated, filtered, and placed in a vacuum oven at 70°C for 24 hours. The total ion content was tested by ICP and recorded in Table 4.

[0128] Table 4 Deashing effect of deashing agent B-3 on COC reaction solution at different reaction space velocities

[0129]

[0130] The experimental results show that the adsorbents prepared by combining thiourea and alginate in Examples 1 to 7 of the present invention have a significant removal effect on the residual metal content in each polymer solution; while the solution using alginate alone as the adsorbent in the comparative example has a very limited removal effect on metallic aluminum, and the solution using thiourea alone as the adsorbent has a very small polymer solution flow rate and cannot reach the set flow rate, and the polymer solution stays in the adsorption column for a long time, indicating that the solution using thiourea as the adsorbent has a too large pressure drop and is not industrially applicable, and its removal effect on residual aluminum metal is obviously not as good as the removal effect of the adsorbent prepared in the embodiments of the present invention.

[0131] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A thiourea-alginate polyolefin material ash removal agent, characterized in that: It has the structure shown in formula I: In formula I, n≥1.

2. A method for preparing the thiourea-alginate polyolefin material ash removal agent according to claim 1, characterized in that: The following steps are involved: The condensation activator and the alginic acid aqueous dispersion are mixed to react, and then thiourea and the condensation agent are added to continue the reaction, and the obtained reactants are filtered, washed, precipitated and dried in sequence to obtain a thiourea-alginic acid polyolefin material ash removal agent; or, Alginate is mixed with N,N-dimethylformamide and thionyl chloride for a first reflux reaction, and then centrifuged to obtain acyl chloride alginate, which is then washed and mixed with thiourea and anhydrous tetrahydrofuran for a second reflux reaction to obtain a thiourea-alginate polyolefin material ash removal agent.

3. The preparation method according to claim 2, characterized in that: The condensation activator is selected from one or more of 4-N,N-dimethylaminopyridine, 1-hydroxybenzotriazole and 4-pyrrolidinopyridine; The mass ratio of the condensation activator to alginic acid is (0.0005-0.3):

1.

4. The preparation method according to claim 2, characterized in that: The condensing agent is selected from one or more of cyclohexylcarbodiimide, diisopropylcarbodiimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide; The mass ratio of the condensing agent to alginic acid is (0.001-0.1):

1.

5. The preparation method according to claim 2, characterized in that: The mass ratio of thiourea to alginic acid is (0.005-5):

1.

6. The preparation method according to claim 2, characterized in that: The reaction temperature is 40°C to 80°C and the reaction time is 50min to 100min; The temperature of the continued reaction is 50° C. to 100° C., and the time is 30 min to 150 min.

7. The preparation method according to claim 2, characterized in that: The volume ratio of the thionyl chloride to the mass ratio of the alginate is (1 mL to 20 mL): 1 g; The mass ratio of thiourea to acyl chloride alginic acid is (0.01-2):

1.

8. The preparation method according to claim 2, characterized in that: The temperature of the first reflux reaction is 40°C to 80°C, and the time is 12h to 24h; The temperature of the second reflux reaction is 70° C. to 75° C., and the time is 18 h to 20 h.

9. An application of an ash removal agent for removing metal ash in a polyolefin reaction liquid, characterized in that: The ash removing agent is the thiourea-alginate polyolefin material ash removing agent according to claim 1 or the thiourea-alginate polyolefin material ash removing agent prepared by the preparation method according to any one of claims 2 to 8.

10. The use according to claim 9, characterized in that: The following steps are involved: The ash removal agent is installed on the solid bed reactor, and the polyolefin reaction liquid is introduced at a reaction temperature of 50°C to 300°C. The flow rate of the polyolefin reaction liquid is 1mL / min to 10mL / min, and the mass ratio of the polyolefin reaction liquid treatment amount to the ash removal agent is (1000 to 100000):1.

Citation Information

Patent Citations

  • Adsorbant for purification of polyolefines and process for prepation thereof

    CN1044415A

  • Decolorizing adsorbent used for purification of polyolefin and preparation method thereof

    CN104587962A